2020
DOI: 10.1002/jso.25902
|View full text |Cite
|
Sign up to set email alerts
|

An economic analysis of prophylactic lymphovenous anastomosis among breast cancer patients receiving mastectomy with axillary lymph node dissection

Abstract: Background and Objectives: Prophylactic lymphovenous anastomosis (LVA) has been shown to decrease the incidence of postoperative lymphedema among patients receiving mastectomy with axillary lymph node dissection (ALND). However, the economic impact of this intervention on overall healthcare costs has not been adequately studied and insurance reimbursement for lymphedema treatment is limited resulting in substantial out-of-pocket patient expenses. Methods:We performed a cost-minimization decision analysis from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“… 46 In our results, AlJindan et al 15 reported that all patients were able to discontinue decompressive therapy postoperatively, whereas Ayestaray et al 23 found this was only true in 30% of patients. Similarly, one study found that ILR results in a greater than 40% cost saving in patients undergoing mastectomy with ALND, 47 as the lifetime cost of lymphedema treatment surpass the upfront cost of ILR.…”
Section: Discussionmentioning
confidence: 96%
“… 46 In our results, AlJindan et al 15 reported that all patients were able to discontinue decompressive therapy postoperatively, whereas Ayestaray et al 23 found this was only true in 30% of patients. Similarly, one study found that ILR results in a greater than 40% cost saving in patients undergoing mastectomy with ALND, 47 as the lifetime cost of lymphedema treatment surpass the upfront cost of ILR.…”
Section: Discussionmentioning
confidence: 96%
“…This sum represented 42% of the total cost per patient in whom no prophylactic intervention was performed. 70 Likewise, in a cost-utility analysis presented by Johnson et al, immediate lymphatic reconstruction after ALND was more cost-effective in comparison to ALND alone, with an incremental cost-utility ratio of $1587.73 per quality-adjusted life year. 71 Similarly, in patients undergoing RLNR, the incorporation of immediate lymphatic reconstruction provided an incremental cost-utility ratio of $699.84 per quality-adjusted life year.…”
Section: Discussionmentioning
confidence: 97%
“…They predicted that if all patients underwent prophylactic bypass, regardless of if the patient developed lymphedema, there was $7646 cost savings (45.2% in their treatment) per patient through limitation of annual medical therapy. 23 …”
Section: Discussionmentioning
confidence: 99%